P51 Evaluation of the advance care planning programme in a cardiac centre in singapore. Issue Volume 9: Issue (2019)Supplement 2 (3rd December 2019) - Lau, CSL; Wong, JCQ; Teo, LY; Khoo, CY; Ng, CT; Chan, LLH; Loh, JK; Lim, SM; CSH, Ng; Tan, SH; Wong, G; Tan, BC; et al.
Abstract : Our institution has initiated inpatient Advance Care Planning (ACP) programme since 2013. However, enrolment rate has been low. We plan to report our experience after extending ACP programme to outpatient setting in 2017. Patients were seen from both inpatient and outpatient setting in 2017 and mainly from outpatient setting from January to June 2018. 115 patients were enrolled out of 1410 patients in 2017 and 84 patients out of 1434 in 2016. This represented 2.3% increase in enrolment rate. From January to June 2018, 376 patients were seen and 69 patients enrolled. Average yield from June 2013 to December 2016 was 5.4%, which was considered low. Patients yield increase from 8.2% in 2017 to 18.4% within the first 6 months of 2018. In 2013 to 2016, we only managed to enrol 6 patients per month. The enrolment rate increase to 10 patients per month in 2017 and 12 patients per month in 2018. There is a significant increase in ACP enrolment rate after shifting our focus from inpatient to outpatient setting. Patients and their caregivers are not ready for ACP conversations during hospitalisation as patients could be too sick to engage in the conversations. They are more willing and receptive to have ACP conversations when they are in outpatient setting. Moving forward, the ACP team will continue to work with primary care providers to offer ACP to patients who need them earlier in their disease trajectory.